2020
DOI: 10.1186/s12870-020-2259-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterising avenin-like proteins (ALPs) from albumin/globulin fraction of wheat grains by RP-HPLC, SDS-PAGE, and MS/MS peptides sequencing

Abstract: Background: Wheat grain avenin-like proteins (ALPs) belong to a recently discovered class of wheat grain storage protein. ALPs in wheat grains not only have beneficial effects on dough quality but also display antifungal activities, which is a novel observation for wheat storage proteins. Previous studies have shown that ALPs are likely present in the albumin/globulin fractions of total protein extract from wheat flour. However, the accumulation characteristics of these ALPs in the mature wheat grain remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…High temperature enhances the total protein content but reduces the end use of protein quality [ 87 , 88 ], which is more or less dependent on the grain protein concentration [ 89 ]. Protein fractions (albumin, globulin, gliadin, and glutenin) are important components for the end use quality of wheat grain [ 90 ]. High temperature at the grain filling duration decreases the albumin and globulin content [ 91 ], whereas it increases the gliadin content at the expense of glutenin content in wheat [ 92 ].…”
Section: Impact Of High Temperature On Wheatmentioning
confidence: 99%
“…High temperature enhances the total protein content but reduces the end use of protein quality [ 87 , 88 ], which is more or less dependent on the grain protein concentration [ 89 ]. Protein fractions (albumin, globulin, gliadin, and glutenin) are important components for the end use quality of wheat grain [ 90 ]. High temperature at the grain filling duration decreases the albumin and globulin content [ 91 ], whereas it increases the gliadin content at the expense of glutenin content in wheat [ 92 ].…”
Section: Impact Of High Temperature On Wheatmentioning
confidence: 99%
“… Jiang et al (2012) conducted a proteomics-based study and reported that the avenin-like proteins expression is highly upregulated under drought stress and may have an essential role in seed quality. Similarly, Zhang et al (2020) suggested that avenin-like proteins are multifunctional including role during disease resistance. In our study, we found very high expression of avenin-like proteins which suggests their important role during seed development/grain filling under heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…While named for their resemblance of oat avenins ( 50 ), these seed storage proteins share sequence similarity and secondary function with γ-gliadins and LMW glutenins ( 51 ). They contribute both to allergenicity ( 52 ) and bread dough quality ( 53 ), and contain one or two gliadin (PF13016) domains. ALPs also contain CD-related B cell epitopes ( 3 ), and their downregulation is important for CD toxicity.…”
Section: Discussionmentioning
confidence: 99%